2006
DOI: 10.1002/pmic.200600084
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related proteome analysis of the mouse brain: a 2‐DE study

Abstract: 2-DE remains the most popular and versatile protein separation method among a rapidly growing array of various proteomics technologies. However, variability in sample processing, experimental design and data analyses results in a limited cross-validation between studies performed in different laboratories. One of the goals of the Human Proteome Organization (HUPO) is to establish standards and guidelines for proteomics studies. We contributed to the HUPO Brain Proteome Project by analyzing brains from neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…For example, only 40 µg of brain segment/injection was used in the study, while hundreds of micrograms of brain segment was required in general brain proteome analysis using 2-DE methods. [26][27][28][29][30] The existence of 28 regionally-specific age-related proteins in mouse brain was demonstrated in this study, seven of which have been reported for the first time. Figure 2 presents a comparison of the peak heights of each of the age-related altered proteins among three aging stages (4, 12 and 20 weeks) in Ctx.…”
Section: )mentioning
confidence: 86%
“…For example, only 40 µg of brain segment/injection was used in the study, while hundreds of micrograms of brain segment was required in general brain proteome analysis using 2-DE methods. [26][27][28][29][30] The existence of 28 regionally-specific age-related proteins in mouse brain was demonstrated in this study, seven of which have been reported for the first time. Figure 2 presents a comparison of the peak heights of each of the age-related altered proteins among three aging stages (4, 12 and 20 weeks) in Ctx.…”
Section: )mentioning
confidence: 86%
“…There have also been other similar HUPO BPP programs [8][9][10][11]. These studies have identified a total of 1,999 spots matched between all gels, among which 206 spots were differentially expressed between the different stages: 122 spots were highest in intensity in embryonic stage E16, 26 were highest in the juvenile group (P7) and 58 spots were highest in the adult stage (P56), revealing a pattern of temporal expression for the examined proteins [107].…”
Section: Current Status Of the Hupo Bpp Activitymentioning
confidence: 97%
“…It is clear that the variability in sample processing, experimental design and data analysis methods results in a limited cross-validation between studies performed in different laboratories, as pointed out by Carrette [8]. Upon the request of the HUman Proteome Organization (HUPO) Brain Proteome Project (BPP) executive committee, Carrette et al identified ten mouse brain proteins: dihydropyrimidinase-related proteins, brain FABP, stathmin, isocitrate dehydrogenase, gamma enolase, annexin V, glutamine synthetase, creatine kinase B chain, triosephosphate dehydrogenase, and malate dehydrogenase [8], most of them functioned in the metabolism of the brain.…”
Section: Proteomic Studies On the Prenatal And Postnatal Stages Of Brmentioning
confidence: 97%
See 1 more Smart Citation
“…treated OA), a class for each group was created using the software. Inter-class data analysis was based on the normalized volume (%vol) to correct for any difference in loading and/or staining [20]. For inter-class differential analysis of healthy (n = 2) vs. treated OA (n = 3) and healthy (n = 2) vs. untreated OA (n = 3), the overlap ratio of the %vol of healthy/untreated OA and healthy/treated OA was calculated for each match.…”
Section: Image Analysismentioning
confidence: 99%